A remote group-mediated daylong physical activity intervention for older adults with chronic pain: Results of the MORPH-II randomized pilot trial - Fanning, Jason; Brooks, Amber K.; Ford, Sherri; Robison, Justin T.; Irby, Megan B.; Rejeski, W. Jack (Frontiers in Digital Health, 2022)
Chronic pain is a debilitating condition that affects many older adults who often have limited access to non-pharmacological pain management strategies. One potentially effective and novel lifestyle medicine for chronic pain involves increasing physical activity through frequent movement across the day, thereby also decreasing the presence of extended sedentary bouts. The MORPH-II pilot randomized controlled refinement trial iterated on the MORPH trial, which was a first-of-its-kind group-mediated daylong physical activity (DPA) intervention for older adults with chronic pain rooted in social cognitive and self-determination theories and supported by an mHealth toolset designed to foster social connection and awareness of physical activity patterns. MORPH-II was delivered fully remotely via videoconference software and supported by a technology kit comprising an iPad, activity monitor, and wireless weight scale. It was also implemented a refined coaching model designed to help participants better understand their own patterns of activity. A total of 44 participants were randomized to receive the 12-week group-mediated DPA intervention or to a low-contact control. Qualitative interviews suggest the program was well-received by participants and that participants developed an understanding of how patterns of physical activity related to their pain symptoms. Participants also highlighted several additional areas for refinement related to the coaching model and feedback provided within the mHealth app. Analyses of covariance, controlling for baseline values, revealed a small effect (η2 = 0.01) on pain intensity favoring the intervention condition, though both groups improved during the study period. There was a large effect favoring the intervention condition on ActivPAL-assessed average daily steps (η2 = 0.23) and postural shifts (η2 = 0.24). Control participants spent less time in short sedentary bouts (η2 = 0.09), and there was a small effect (η2 = 0.02) indicating intervention participants spent less time in extended sedentary bouts. Finally, relative to control, intervention participants demonstrated a moderate improvement in autonomy satisfaction (η2 = 0.05), relatedness frustration (η2 = 0.05), and competence frustration (η2 = 0.06), and a large magnitude improvement in competence satisfaction (η2 = 0.22). These findings indicate that the MORPH-II intervention was feasible and acceptable, and may positively impact steps, postural breaks, and several key domains of basic psychological needs detailed in self-determination theory.